2015
DOI: 10.1111/bjop.12166
|View full text |Cite
|
Sign up to set email alerts
|

Laterality effects in the spinning dancer illusion: The viewing‐from‐above bias is only part of the story

Abstract: The 'silhouette illusion', representing the silhouette of a female dancer pirouetting about her vertical axis, is a bistable stimulus created by Japanese web designer Nobuyuki Kayahara. Although the dancer can be perceived as spinning either clockwise or counterclockwise, the clockwise rotation is usually preferred. Troje and McAdam (i-Perception, 2010, 1, 143) showed that this clockwise bias can be attributed to the tendency to assume a viewpoint from above rather than from below, given that the dancer is por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 48 publications
11
23
2
Order By: Relevance
“…Indeed, inversion, which is known to disrupt the configural processing of human bodies (e.g., Reed et al, 2003, 2006), abolished the bias to perceive right-handed actions found in the upright session. As predicted, and in line with our previous findings showing that the bias toward the right limb of human bodies is consistent across different types of stimuli and response modalities (Marzoli et al, 2015; Lucafò et al, 2016), the effect of session did not differ across the different tasks, which supports the robustness of our results. Our study thus provides an additional instance of the detrimental effects of body inversion on configural processing, such as reduction in perceptual grouping (Poljac et al, 2011, 2012), body posture recognition (Reed et al, 2003, 2006), action recognition (Dittrich, 1993) and emotion recognition from whole-body gestures and dance movements (Dittrich et al, 1996; Atkinson et al, 2007), as well as the abolishment of expertise-related advantage in action discrimination (Calvo-Merino et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Indeed, inversion, which is known to disrupt the configural processing of human bodies (e.g., Reed et al, 2003, 2006), abolished the bias to perceive right-handed actions found in the upright session. As predicted, and in line with our previous findings showing that the bias toward the right limb of human bodies is consistent across different types of stimuli and response modalities (Marzoli et al, 2015; Lucafò et al, 2016), the effect of session did not differ across the different tasks, which supports the robustness of our results. Our study thus provides an additional instance of the detrimental effects of body inversion on configural processing, such as reduction in perceptual grouping (Poljac et al, 2011, 2012), body posture recognition (Reed et al, 2003, 2006), action recognition (Dittrich, 1993) and emotion recognition from whole-body gestures and dance movements (Dittrich et al, 1996; Atkinson et al, 2007), as well as the abolishment of expertise-related advantage in action discrimination (Calvo-Merino et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…This expedient was aimed at reducing the possible carry-over of responses from trial to trial (e.g., see Liu et al, 2012, who found percept carry-over even after a 30 s break between the presentation of an ambiguous spinning body and the next one). As in a previous study with the spinning dancer illusion (Lucafò et al, 2016), we decided to collect participants’ responses by means of two colored arrows, each representing a possible spinning direction, rather than by means of simple vocal responses such as “ORARIO” (the Italian word for “CLOCKWISE”) and “ANTIORARIO” (“COUNTERCLOCKWISE”), because the latter response modality seems to be rather troublesome for participants (maybe due to their difficulty in labeling as clockwise or counterclockwise a rotation about an axis approximately parallel to their own body axis). Before the task, in order to familiarize participants with the response modality, they were administered a pretest in which they had to use the two response arrows to indicate the spinning direction of a black human silhouette containing perspective cues (e.g., the relative size of the hands in different positions).…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations